FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN PEMBELIAN PRODUK REKSADANA SYARIAH DI APLIKASI BIBIT - Aliifah, Shofi; Galuh, Ajeng kartika (Islamic Economics and finance in Focus, 2023)
Both in terms of quantity and NAV based on the OJK report as of August 2022, the level of sharia mutual funds is still relatively low in comparison to conventional mutual funds. According to KSEI data as of June 2022, investors primarily belong to the millennial and Z generations. This is a result of how convenient financial technology has made investing, and one of Indonesia's most well-known investment businesses is Bibit. This study aims to identify the elements that millennial and Z generations use to decide whether to buy sharia mutual fund products using the Bibit application. In this quantitative study, 96 individuals who have acquired Islamic mutual fund products range in age from 17 to 40. According to the findings of logistic regression research, financial capability, returns, and Islamic financial literacy simultaneously have an impact on consumers' purchasing decisions. Partially, Islamic financial literacy and ability have no discernible impact, whereas return has a positive and significant impact. As a result, it is known that return is the primary factor in millennial and Z generations' decisions to purchase Islamic mutual fund products through the Bibit application.